Adaptação organizacional e gestão de recursos públicos: o caso do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe diante das incertezas no ambiente orçamentário - França, Mariana Carla Lima (2024)
Objective: this study aimed to diagnose how the Federal Institute of Education, Science and Technology of Sergipe (IFS) adapts to and responds to uncertainties in the budgetary environment, regarding the allocation and management of public resources. Methodology: the present research has a descriptive nature, a qualitative approach, and is characterized as a case study. For data collection, these were obtained through documentary analysis and interviews with the managers of the IFS institute, to understand the adaptation strategies and how they affect organizational performance, as well as the governance strategies adopted to plan for and deal with uncertainties in the budgetary environment. The collected information was processed and analyzed. As research techniques, documentary analysis and content analysis were used. Main results: it was noted that the strategies used for resource allocation focused on rationing and suspending expenses, selecting and analyzing priorities, as well as other strategies such as raising offbudget funds, reallocating resources, and seeking partnerships and donations. It was found that the recruitment strategies were the only ones that influenced the organizational performance of the Campuses. Regarding uncertainties, it can be said that they are taken into account in budget planning; however, it was possible to understand that it is a complicated task even in the face of the difficulties of predicting future events. Theoretical contribution: the theoretical contribution of this study is the understanding of how the IFS has been facing this moment of resource scarcity. Social and management contributions: information may help other federal higher education institutions identify their obstacles and contingent factors for a more efficient and appropriate budget management, focusing on environmental planning and analysis.